Medicinal plants used by residents of an area of thorny deciduous woodland, Ceará, Brazil (Research, Society and Development, 2020)
Objective: conduct an ethnobotanical study of medicinal plants used by a rural community located in an area of thorny deciduous forest (Caatinga) in Altaneira, Ceará, Brazil, identify the species, the diversity of uses, the most versatile species, the therapeutic indications and body systems, as well as indicating the species used in traditional medicine, described in the literature as harmful to health if used improperly. Methodology: the research took place from november 2013 to february 2014. To obtain ethnobotanical data, interviews were conducted with the aid of a questionnaire with semi-structured questions. To assess versatility in use, the relative importance (RI) of the plants cited by local informants was analyzed and the species that stood out in the body systems were evaluated based on the informant's consensus factor. Results: A total of 79 species in 36 families used to treat 75 diseases was recorded. The most significant families in number of species were Fabaceae (10), Asteraceae (8), Lamiaceae (8), Rutaceae (4) and Euphorbiaceae (4). Among the species listed, those which presented RI value> 1 were Bryophyllum pinnatum, Mentha spicata, Rosmarinus officinalis Melissa officinalis, Ruta graveolens, Myracroduon urundeuva, Amburana ceaerensis, Helianthus annuus, Plectranthus amboinicus, Brassica rapa. Conclusion: These species may be suitable for pharmacological studies, in order to prove their efficacy and / or toxicity, aiming safer use.